2021
DOI: 10.1007/s13312-021-2244-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities on Outcome in Children With COVID-19 at a Tertiary Care Pediatric Hospital

Abstract: Objective To study the various comorbidities and their impact on outcome of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected children. Methodology Review of medical records of 120 children (58.4% males), aged 1 month to 18 years, admitted between 1 March and 31 December, 2020 with at least one positive RT-PCR test for SARS-CoV-2. Clinical and demographic variables were compared between children with and without co-morbidities. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
3
15
0
2
Order By: Relevance
“…One (2.3%) study did not specify the inclusion criteria [ 46 ]. Only two (4.7%) studies specifically evaluated children [ 63 , 71 ]; others included only adults or described a mixed population. Patient information was retrieved mainly from medical records at participating healthcare facilities, or from surveillance registries or insurance databases ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One (2.3%) study did not specify the inclusion criteria [ 46 ]. Only two (4.7%) studies specifically evaluated children [ 63 , 71 ]; others included only adults or described a mixed population. Patient information was retrieved mainly from medical records at participating healthcare facilities, or from surveillance registries or insurance databases ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies with 42,321 COVID-19 patients, of whom 632 (1.5%) had tuberculosis, reported on deaths due to COVID-19 [ 36 , 39 , 41 43 , 45 , 47 50 , 52 , 57 , 60 , 63 , 65 67 ]. All studies were conducted in high tuberculosis burden countries, except one from South Korea and another that combined data from multiple nations [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study from our institute Kapoor, et al . [ 8 ], reported a prevalence of 9.27% SARS-CoV-2 positivity in cases admitted in paediatric medicine wards.…”
Section: Discussionmentioning
confidence: 99%
“…These data are similar to that reported by Kapoor, et al . [ 8 ] from our institute, where they had observed that the presence of a comorbid illness in paediatric inpatients with SARS-CoV-2 infection did not impact the illness severity, length of hospitalization, ventilation requirement and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…23 Penelitian kami menunjukkan bahwa derajat berat-kritis didominasi oleh pasien dengan komorbid, meskipun begitu berdasarkan analisis tidak didapatkan hubungan bermakna. Hal ini selaras dengan penelitian Kapoor dkk 24 yang melaporkan tidak ada perbedaan antara derajat keparahan COVID-19 pada anak dengan komorbid dan tanpa komorbid.…”
Section: Pembahasanunclassified